Systematic reviews of clinical practice guidelines: a methodological guide - Johnston, Amy; Kelly, Shannon E.; Hsieh, Shu-Ching; Skidmore, Becky; Wells, George A. (Université d'Ottawa | University of Ottawa, 2018)
Systematic reviews (SRs) of clinical practice guidelines (CPGs) are unique knowledge syntheses that require tailored approaches to, and greater subjectivity in, design and execution compared to other SRs in clinical epidemiology. We provide review authors structured direction on how to design and conduct methodologically rigorous SRs of CPGs.
Keywords: clinical practice guidelines; evidence-based medicine; research methodology; systematic review